Предмет: Алгебра,
автор: Аноним
найти х, если (х+1)(х+2)(х+3)(х+4)=3
Ответы
Автор ответа:
0
{(x+1)(x+4)}{(x+3)(x+2)}=3
(x^2+5x+4)(x^2+5x+6)=3
Замена x^2+5x=a
(a+4)(a+6)=3
a^2+10a+21=0
a1=-3 a2=-7
Обратная замена
x^2+5x=-3 x^2+5x=-7
x^2+5x+3=0 x^2+5x+7=0
D=13 D=-3 нет решения
x1=-5+корень13/2
x2=-5-корень13/2
Ответ: x1=-5-корень13/2
x2=-5+корень13/2
(x^2+5x+4)(x^2+5x+6)=3
Замена x^2+5x=a
(a+4)(a+6)=3
a^2+10a+21=0
a1=-3 a2=-7
Обратная замена
x^2+5x=-3 x^2+5x=-7
x^2+5x+3=0 x^2+5x+7=0
D=13 D=-3 нет решения
x1=-5+корень13/2
x2=-5-корень13/2
Ответ: x1=-5-корень13/2
x2=-5+корень13/2
Похожие вопросы
Предмет: Математика,
автор: kkapenova7
Предмет: Литература,
автор: qqwairz
Предмет: История,
автор: 1984zxcxzc1984
Предмет: Химия,
автор: alina07041